Immune-checkpoint inhibitors associated with interstitial lung disease in cancer patients. Issue 2 (10th August 2017) - Delaunay, Myriam; Cadranel, Jacques; Lusque, Amélie; Meyer, Nicolas; Gounaut, Valérie; Moro-Sibilot, Denis; Michot, Jean-Marie; Raimbourg, Judith; Girard, Nicolas; Guisier, Florian; Planchard, David; Metivier, Anne-Cécile; et al.
Immunotherapy is becoming a standard of care for many cancers. Immune-checkpoint inhibitors (ICI) can generate immune-related adverse events. Interstitial lung disease (ILD) has been identified as a rare but potentially severe event. Between December 2015 and April 2016, we conducted a retrospective study in centres experienced in ICI use. We report the main features of ICI–ILD with a focus on clinical presentation, radiological patterns and therapeutic strategies. We identified 64 (3.5%) out of 1826 cancer patients with ICI–ILD. Patients mainly received programmed cell death-1 inhibitors. ILD usually occurred in males, and former or current smokers, with a median age of 59 years. We observed 65.6% grade 2/3 severity, 9.4% grade 4 severity and 9.4% fatal ILD. The median (range) time from initiation of immunotherapy to ILD was 2.3 (0.2−27.4) months. Onset tended to occur earlier in lung cancer versus melanoma: median 2.1 and 5.2 months, respectively (p=0.02). Ground-glass opacities (81.3%) were the predominant lesions, followed by consolidations (53.1%). Organising pneumonia (23.4%) and hypersensitivity pneumonitis (15.6%) were the most common patterns. Overall survival at 6 months was 58.1% (95% CI 37.7–73.8%). ICI–ILD often occurs early and displays suggestive radiological features. As there is no clearly identified risk factor, oncologists need to diagnose and adequately treat this adverse event. Awareness of clinical/radiological presentation of immunotherapy-related pneumonitis is crucial to ensure a diagnosis http://ow.ly/eIMF30bgolf